Coping Strategies On Wives in a Long-Distance Marriage And Live with In-laws - Nareswari Diah Wijang Wardhani; Putu Nugrahaeni Widiasavitri (Universitas Katolik Soegijapranata, 2020)
This study aims to find out the coping strategy of wives who living the two phenomena of married life that are famous with the conflict, which is, long distance marriage and living with parent in-laws. This research used a qualitative approach, a phenomenological method. Respondents in this study were 3 wives undergoing long-distance marriages with no more than 5 years of marriage and lived with parent in-laws. Data collection used individual interviews and observations. The results shows that the wife did a coping strategy in living her married life. Social support, seeking busyness, making children as an excuse to maintain the marriage, self-fulfilling prophecy, delaying problem-solving, succumb to in-laws, and trusting with husband. Coping strategies are influenced by several factors such as a picture of future hopes, feelings of longing, love, and marriage commitments. As for the inhibiting factors, including intervention from in-laws and limited meetings with husbands.